Comparative study of the compensated semi-metals LaBi and LuBi: a first-principles approach. (20th April 2018) - Dey, Urmimala
Abstract: We have investigated the electronic structures of LaBi and LuBi, employing the full-potential all electron method as implemented in Wien2k. Using this, we have studied in detail both the bulk and the surface states of these materials. From our band structure calculations we find that LuBi, like LaBi, is a compensated semi-metal with almost equal and sizable electron and hole pockets. In analogy with experimental evidence in LaBi, we thus predict that LuBi will also be a candidate for extremely large magneto-resistance (XMR), which should be of immense technological interest. Our calculations reveal that LaBi, despite being gapless in the bulk spectrum, displays the characteristic features of a topological semi-metal, resulting in gapless Dirac cones on the surface, whereas LuBi only shows avoided band inversion in the bulk and is thus a conventional compensated semi-metal with extremely large magneto-resistance.